Organization Of Practical Processes In The Development Of Physics Laboratories, Problems And Solutions Of Research Direction For Students (Journal of Pedagogical Inventions and Practices, 2024)
In our country, education and science have been taught with limited theoretical knowledge, while the cluster approach is based on the initiative of institutions or organizations, as a form of their social cooperation, the creation of a unified education system is underway. There is a need to combine the resources and capabilities of organizations that are part of the educational cluster to improve the quality and competence of graduates, to introduce new technologies for teaching and training